Antibiotic Susceptibility of Klebsiella pneumoniae isolated from Selected Tertiary Hospitals in Osun State, Nigeria - Adeosun, Idowu Jesulayomi; Oladipo, Kolawole Elijah; Ajibade, Oluwatosin Akinola; Olotu, Titilayo Mabel; Oladipo, Abayomi A; Awoyelu, Elukunbi Hilda; Alli, Oyebode Armstrong Terry; Oyawoye, Olubukola Monisola (Iraqi Journal of Science, 2019)
Klebsiella pneumoniae is a pathogen of the Enterobacteriaceae family that causes healthcare-associated infections and has recently emerged as one of the most antibiotic-resistant organisms responsible for outbreaks in both community and healthcare settings. The aim of this study is to determine the resistance pattern of Klebsiella pneumoniae isolated from selected tertiary hospitals in Osun state, Nigeria. A total of 62 Klebsiella pneumoniae isolates were obtained from 1056 samples of urine, wound swab, ear swab, eye swab and other collection sites that were routinely submitted to the diagnostic laboratories of the selected tertiaryhospitals. Susceptibility to twelve (12) antibiotics (Oxoid) was determined using the Kirby Bauer disk diffusion method for the 62 isolates. Rate of resistance to carbapenems, fluoroquinolones, polymyxins, monobactams, cephalosporins, penicillin and phosphonic acid derivative are 29.03%, 47.84%, 29.03%, 46.77%, 50.80%, 93.55%, and 37.10% respectively. The isolates were mostly susceptible to carbapenems, especially, Imipenem with 74.19%. Highest resistance was to Penicillin (93.55%). The multiple antibiotic resistance (MAR) index revealed that 52 (83.87%) out of 62 isolates were multi-drug resistant. Increase in antibiotic resistance continues to be a problem amidst patients infected with Klebsiella pneumoniae which can be most likely attributed to increase in antibiotic misapplication, misuse and abuse which is most prevalent among youths. It is therefore of utmost importance that consistent monitoring of antibiotic resistance be done as it will assist in the appropriate selection of empiric antibiotic treatment in the proper setting.